2008
DOI: 10.1148/radiol.2482071578
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal Papillary Mucinous Neoplasm of the Pancreas: Assessment of the Likelihood of Invasiveness with Multisection CT

Abstract: Multisection CT is useful for distinguishing among adenoma, noninvasive carcinoma, and invasive carcinoma in patients with IPMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 44 publications
4
62
2
1
Order By: Relevance
“…The sensitivity, specificity, and accuracy of MDCT in characterizing the malignancy of IPMNs were 100%, 87.5% and 95%, respectively. They were a little bit higher than the data in the published literature [2,15] . This could be explained possibly by the bias generated by the small number of purely main duct IPMNs and the limited size of the entire patient population in this group.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The sensitivity, specificity, and accuracy of MDCT in characterizing the malignancy of IPMNs were 100%, 87.5% and 95%, respectively. They were a little bit higher than the data in the published literature [2,15] . This could be explained possibly by the bias generated by the small number of purely main duct IPMNs and the limited size of the entire patient population in this group.…”
Section: Discussioncontrasting
confidence: 56%
“…Thinner-slice reformed CTA and MPVR or CR images showed other malignant signs clearly, including vascular invasion, lymph node enlargement, and duodenal involvement, as well as dilatation of the common bile duct and common hepatic duct (Figure 3). Ogawa et al [15] reported that the sensitivity, specificity, and accuracy for identifying malignancy were 83%, 81% and 82% and for identifying pancreatic parenchymal invasion were 90%, 88% and 89%, respectively. According to the International Consensus Guidelines for management of IPMN, the branch duct IPMNs are benign more frequently than the main duct IPMNs [2] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Of these studies, 33 investigated mural nodules5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 21 examined dilatation of the main pancreatic duct (MPD)7 9, 15 16, 18 21, 23 26, 27 30, 32 36, 38, 39, 40, 41, 42, 43, 44, 45, 46, 21 analysed cyst size5 7, 8, 9 14, 15 18, 20 23, 25 27, 28 31, 36 38, 40 41, 43 47, 48, 49, 17 assessed CA19‐9 increase…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, both CT scan and MRI with MRCP have demonstrated high accuracy (Figs. 3 and 4); however, magnetic resonance is more effective in depicting the communication between the IPMN and the ductal system [28,29]. EUS can be used as a second level examination in patients with "worrisome features" (cyst >3 cm, thickened enhanced cyst walls, MPD size of 5-9 mm, non-enhanced mural nodules, abrupt change in the MPD caliber, and lymphadenopathy) for detecting mural nodules and it allows fluid aspiration and targeted biopsies.…”
Section: Intraductal Papillary Mucinous Neoplasmmentioning
confidence: 99%